Seniorzy w cyberprzestrzeni. Między stereotypem a rzeczywistością - Błeszyńska, Krystyna M.; Orłowska , Małgorzata (Studia Edukacyjne, 2020)
Błeszyńska Krystyna M., Orłowska Małgorzata, Seniorzy w cyberprzestrzeni. Między stereotypem a rzeczywistością [Seniors in Cyberspace. Between Stereotype and Reality]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 153-166. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.8 Today, stereotypically seniors are assigned many negative traits. One of them is their lack of digital competences, which in consequence leads to their exclusion from modern social life. Given that modern Western societies are rapidly aging, this problem is becoming a social issue that needs to be addressed. A significant part of society must not be allowed to live as outcasts. In this situation, a question arises whether contemporary seniors are definitively excluded, or is age not an apparent premise in their case, and the problem lies elsewhere? The analysis of the collected empirical material revealed that the variable determining the level and type of social participation in virtual society is not age, but the level of education. Therefore, contrary to the prevailing views, seniors are not at risk of information exclusion and it is difficult to consider them as digital immigrants. Contrary to stereotypes, seniors are more distant, selective and pragmatic; independence allows them not to imitate culture and lifestyles, but to create them in contrast to the generation of their grandchildren.